Potential of Ethanol Extract of Red Ginger (Zingiberis officinale) as Antioxidant Using FRAP (Ferric Reducing Antioxidant Power) Method - Amin, Nur Hikmawati (Makassar Natural Product Journal (MNPJ), 2024)
Red ginger (Zingiber officinale var. Rubrum) is one of the spices that also has potential as a medicinal plant and is also efficacious as an antioxidant. Antioxidants are chemical compounds that donate electrons to unpaired free radicals, thus reducing the oxidizing effect of free radicals. This study aims to determine the potential of ethanol extract of red ginger (Zingiber officinale var. Rubrum) as an antioxidant using the FRAP method. Red ginger extracted by maceration technique using 96% ethanol solvent was measured using UV-Vis spectrophotometer instrument at a maximum wavelength of 689 nm. From this study, the percent yield of 9.055%, regression equation y = 0.0154x - 0.5374, r = 0.99508 and antioxidant activity of 142.172 mg/AAE were obtained.